Concussion incidence in amateur Australian Rules Footballers. (October 2018) - Costello, Daniel M.; Ernest, Joel; Kaye, Andrew H.; O'Brien, Terence J.; Shultz, Sandy R.
Highlights: Sport-related concussion. Mild traumatic brain injury. Incidence. Australian Rules Football. Athlete exposures. Abstract: Australian Rules Football is a collision sport that is associated with increased sport-related concussion risk. Sport-related concussion is a common form of mild traumatic brain injury that is now recognised as a serious health issue. This study measured the concussion incidence rate for amateur Australian Rules players over 3 seasons (2015–2017) by athlete exposures—a metric used widely in the literature. This study also reported concussion incidence based on player match hours, a less common yet more accurate method of reporting concussion incidence which takes match duration into account. Accurate concussion incidence reporting in amateur Australian Rules Football quantifies the problem of concussion in this sport. This may be necessary to inform players of their concussion injury risk and to help guide rule changes to protect players from this injury.